Education Management Strategy in Medan City: Improving The Quality of Learning Through Innovation and Collaboration - Lubis, Hasrita; Asyira, Nurul; Pane, Sri Gustina (Universitas Syiah Kuala, 2025)
This study aims to analyze education management strategies in Medan City in an effort to improve the quality of learning through innovation and collaboration. Using a qualitative approach and descriptive methods, this study collects data through in-depth interviews, participatory observations, and documentation studies from various education stakeholders, including school principals, teachers, education officials, and the community. The main findings of the study show that the application of information technology, the development of local competency-based curriculum, and innovative teaching methods have improved student motivation and teaching quality. Collaboration between schools, the government, the private sector, and the community has also contributed positively to improving the quality of education. However, the study also identifies constraints such as limited infrastructure, varied community participation, and complex bureaucracy as challenges in the implementation of strategies. Research recommendations include improving infrastructure, increasing community participation, and simplifying bureaucracy to support the success of education management strategies. This research provides insight into the effectiveness of innovation and collaboration in education as well as the steps needed to overcome obstacles and maximize educational outcomes in Medan City.